Institusionalisasi Partai Politik: Studi Kasus Partai Demokrat di Era Kepemimpinan Agus Harimurti Yudhyono Periode 2020-2022 - Hasibuan, Arif Darmawan; Pasha Rasjid, Julian Aldrin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research discusses the institutionalization of the Democratic Party in the leadership era of Agus Harimurti Yudhyono (AHY) for the 2020-2022 period. The research results show that the Democratic Party in the era of AHY's leadership for the 2020-2022 period has made various efforts to realize ideal party institutional strengthening. However, the identification of the Democratic Party as a Family Party with the placement of Susilo Bambang Yudhyono (SBY) as Chair of the Party High Council and Edi Baskoro Yudhyono (Ibas) as Chair of the Party Fraction in the structure of the Democratic Party's Central Leadership Council (DPP) for the 2020-2025 period is a challenge in itself. the process of strengthening the party's institutions. Nevertheless, the results of this research show that the Democratic Party in the era of AHY's leadership for the 2020-2022 period has a relatively strong level of institutionalization. This shows that, even though the Democratic Party is identified as the Family Party, the influence of the family party factor does not have a significant impact on the institutional weakening of the Democratic Party in the era of AHY's leadership for the 2020-2022 period. This research uses Randall and Svasand's theory of political party institutionalization through internal aspects viewed from the systemic dimension and external aspects viewed from the public image dimension. Meanwhile, to identify the Democratic Party as a Family Party, the theory and concept of the Family Party from Peter Mair and Case Mudde is used through the dimensions of the party's origins and ideology.